PROSPECTS FOR INCREASING INVESTMENT ATTRACTIVENESS IN ENSURING FINANCIAL STABILITY OF REGIONS - Sunatullayeva Shahnoza Xurshid qizi (Web of Journals Publishing, 2024)
Enhancing investment attractiveness is paramount for ensuring the financial stability and prosperity of regions in today's global economy. This article explores the multifaceted strategies essential for bolstering investment attractiveness, including fostering an enabling business environment, investing in infrastructure and innovation, ensuring socio-political stability, harnessing international collaboration, and embracing sustainable development. By implementing these strategies, regions can attract capital inflows, stimulate economic growth, and navigate the complexities of an ever-evolving economic landscape, ultimately fostering resilient and inclusive societies.
Keywords: Investment attractiveness, financial stability, regions, enabling business environment, infrastructure development, innovation, socio-political stability.